2012
DOI: 10.1603/ec12078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ipsdienol, Ipsenol, and <I>cis</I>-Verbenol in Chemical Ecology of <I>Ips avulsus</I>, <I>Ips calligraphus</I>, and <I>Ips grandicollis</I> (Coleoptera: Curculionidae: Scolytinae)

Abstract: Stressed or damaged pine (Pinus sp.) trees in the southeastern United States are often colonized simultaneously by three southern Ips species (Coleoptera: Curculionidae: Scolytinae): small southern pine engraver, Ips avulsus (Eichhoff); sixspined ips, Ips calligraphus (Germar); and eastern Þvespined ips, Ips grandicollis (Eichhoff). All three species mediate colonization of host material with volatile pheromones. All of the southern Ips produce cis-verbenol, and either ipsdienol or ipsenol, and electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Among many insects, the behavioral mechanisms that facilitate pair formation are hypothesized to be the same as those that prevent hybridization. For example, specificity of pheromone response has been hypothesized to mediate mate location and reproductive isolation in bark beetles (Lanier and Wood 1975; but see Allison et al 2012b). The observation that the sympatric species M. carolinensis and M. titillator rely on the same mechanism for mate location (monochamol) suggests that in these species, the mechanisms involved in mate location and reproductive isolation may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Among many insects, the behavioral mechanisms that facilitate pair formation are hypothesized to be the same as those that prevent hybridization. For example, specificity of pheromone response has been hypothesized to mediate mate location and reproductive isolation in bark beetles (Lanier and Wood 1975; but see Allison et al 2012b). The observation that the sympatric species M. carolinensis and M. titillator rely on the same mechanism for mate location (monochamol) suggests that in these species, the mechanisms involved in mate location and reproductive isolation may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence supporting this hypothesis is provided in this study based on the observed frequencies of I. avulsus and I. grandicollis (represented by the LSD lure combination) relative to I. calligraphus (represented by the VD lure combination), with higher combined seasonal trap catches of I. avulsus and I. grandicollis equaling 234,180 compared with 48,581 individuals of I. calligraphus. Lower numbers of I. calligraphus relative to I. avulsus and I. grandicollis have been observed in other studies as well (e.g., Miller et al 2011, Allison et al 2012b. Additional trapping studies are necessary to fully test this hypothesis.…”
Section: Discussionmentioning
confidence: 62%
“…It was, however, worthwhile to note when clear preferences were observed. The lure combinations used in this study were modiÞed from earlier studies targeting the southern Ips species (Miller et al 2005, Allison et al 2012b) and were successful in attracting each of the target species, with relatively few individuals collected in traps baited with the other lure combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ipsenol and cis‐ verbenol play an important role as aggregating pheromones for both sexes (Vité & Renwick ; Neumann & Morey ; Dodds & Miller ; Allison et al . 2012b). Ipsenol is the key pheromone component for both sexes, while E ‐myrcenol is only detected by female beetles and may act as a sex pheromone, rather than an aggregation pheromone component (Birgersson et al .…”
Section: Biology and Ecologymentioning
confidence: 99%